Effects of Recreational Swimming on Blood Pressure and Lower Extremity Muscle Strength of Older Adults With Elevated Blood Pressure: A Sample of Altınova Beachgoers - Cemal Polat (Pamukkale Spor Bilimleri Dergisi)
This study aimed to investigate the effects of recreational swimming (RS) on blood pressure (BP) and lower extremity muscle strength (LEMS) in older adults with elevated blood pressure (EBP). A total of 44 elderly people, 21 men (x̄age=70.6 years, sd= 1.07; body mass index (BMI)=27.4 kg/m2, sd=0.67) and 23 women (x̄age=70.2 years, sd=1.15; BMI=28.6 kg/m2, sd=0.92) participated in the study. Participants were reached by snowball sampling method. Data were collected using a semi-automated BP monitor and Chair Stand Test. Analyses were performed using mixed-design ANOVA with a significance level of p